Kebijakan Kepolisian Sektor Pemayung dalam Penyelesaian Tindak Pidana Penganiayaan Secara Restoratife Justice - Ahmad Zulfikar (Universitas Batanghari Jambi, 2021)
Efforts to overcome crime through peace based on Restorative Justice, namely justice for all parties are greatly missed by everyone. In carrying out law enforcement duties, the State Police Investigator of the Republic of Indonesia has the duties, functions, and authorities in the field of investigating criminal acts in accordance with the applicable laws and regulations. Based on the Regulation of the National Police Chief Number .6 of 2019 concerning Criminal Investigation, it has a role to carry out prevention efforts without having to use the Criminal Justice System (SPP), namely by resolving cases through the peace process. This process is due to the desire of the community who wants the case to be completed immediately and no longer be complicated. The resolution can be supported by the police's discretionary authority so that the type of research is descriptive empirical juridical, using primary data by means of interviews and secondary data by means of documentation studies. Then all data were processed using qualitative data analysis. Based on the research results, the Pemayung Police Sector policy is to settle criminal cases peacefully (penal police), or through the settlement of criminal cases involving the perpetrator, victim and/or their family and related parties, with the aim of achieving justice for all parties/restorative justice can be carried out, if it does not cause public unrest or there is no community rejection, it will not have an impact on social conflict and the case is still in the process of investigation and investigation. So that it can be directed to a settlement by conducting mediation to the parties, both the victim and the suspect. From the results of the mediation, it was agreed by the parties, both from the reporting party and the reported party as a suspect, admitting all his actions. And from the results of the mediation there was an agreement with the parties (victim and suspect) and a letter of peace was made and the revocation of the Police Report by the victim but after that, the victim came and asked again for the case to be continued, the investigator explained that the agreement had become an agreement of both parties and was binding and the investigation has been discontinued.